Phthalates deregulate cell proliferation, but not neuroendocrine transdifferentiation, in human LNCaP prostate cancer cell model - Hrubá, E; Pernicová, Zuzana; Pálková, L; Souček, Karel; Vondráček, Jan; Machala, Miroslav (Folia biologica (Praha), 2014)
Phthalate esters are ubiquitous environmental pollutants widely used as plasticizers, which have been shown to interfere with both endocrine regulation and development of reproductive organs. In the present study, we examined the impact of diethylhexyl phthalate (DEHP) and dibutyl phthalate (DBP) on the proliferation of androgen-sensitive human prostate carcinoma LNCaP cells and related events. The results showed that both compounds were able to inhibit cell cycle progression in a dose-dependent manner. However, only DEHP was found to weakly reduce androgen receptor (AR) protein levels after long-term exposure, while only DBP partially inhibited expression of the prostate-specific antigen (KLK3) gene, a model AR transcriptional target. This indicated that inhibition of cell proliferation was likely independent of any AR modulations. Both phthalates induced suppression of cell proliferation, but none of them affected the levels of markers associated with neuroendocrine transdifferentiation (NED) in LNCaP cells. Taken together, the presented data indicate that phthalates may exert long-term negative effects on the proliferation of prostate epithelial cells derived from the carcinoma model, which are, nevertheless, largely independent of the modulation of AR expression/activity, and which do not alter further processes associated with NED.
Keywords: regulace genové exprese u nádorů; prostatický specifický antigen; biologické modely; Cell Count; proliferace buněk; Cell Line, Tumor; diethylhexylftalát; Cell Cycle; Gene Expression Regulation, Neoplastic; lidé; neuroendokrinní buňky; Models, Biological; Neuroendocrine Cells; messenger RNA; nádory prostaty; Prostatic Neoplasms; Diethylhexyl Phthalate; Prostate-Specific Antigen; buněčný cyklus; RNA, Messenger; Dibutyl Phthalate; Male; Cell Proliferation; Phthalic Acids; počet buněk; dibutylftalát; mužské pohlaví; kyseliny ftalové; Cell Transdifferentiation; nádorové buněčné linie; transdiferenciace buněk; Humans